2020
DOI: 10.3390/d12120466
|View full text |Cite
|
Sign up to set email alerts
|

Indo-Pacific Phylogeography of the Lemon Sponge Leucetta chagosensis

Abstract: The sponge Leucetta chagosensis Dendy (1913) has a wide distribution throughout the Indo-Pacific (IP) region, with previous studies focussing primarily on the western Pacific Ocean. To increase our knowledge of the spatial variation of genetic diversity throughout the IP, we constructed a phylogeny for L. chagosensis for the IP to assess the evolutionary patterns for this species. We generated 188 sequences of L. chagosensis and constructed maximum likelihood and Bayesian inference trees, using concatenated mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…The intraspecific p-distance among them was 0.0-2.3% for the C-LSU and 1.5% for the ITS. This relatively high p-distance and wide-spread scenario suggest that L. chagosensis may be a complex of cryptic species, as already proposed by Wörheide et al (2002Wörheide et al ( , 2008, Klautau et al (2020) and Pasnin et al (2020). Our results indicate that L. villosa is part of this complex (see the 'Taxonomic remarks' of L. chagosensis).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…The intraspecific p-distance among them was 0.0-2.3% for the C-LSU and 1.5% for the ITS. This relatively high p-distance and wide-spread scenario suggest that L. chagosensis may be a complex of cryptic species, as already proposed by Wörheide et al (2002Wörheide et al ( , 2008, Klautau et al (2020) and Pasnin et al (2020). Our results indicate that L. villosa is part of this complex (see the 'Taxonomic remarks' of L. chagosensis).…”
Section: Resultssupporting
confidence: 83%
“…Of course, it is possible that L. chagosensis is a species complex. A recent work using more variable markers (Pasnin et al, 2020) found five lineages restricted to different biogeographic regions. The authors said they did not find morphological differences, but no morphological analyses were presented and they did not propose to split L. chagosensis.…”
Section: Geographic Distribution: Indian Ocean: Chagosmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to environmental parameters to explain the distribution of a species (Økland & Økland 1996;Evans & Montagnes 2019) there is also the historical component, which Avise and co-workers (Avise et al 1987) designated intraspecific phylogeography. There have not been many studies of phylogeography in marine sponges (Wörheide et al 2002;Duran et al 2004;Nichols & Barnes 2005;Becking et al 2013;Pasnin et al 2020) and but a few for freshwater sponges (Schröder et al 2003;Lucentini et al 2013). Although assessing phylogeography in the marine environment is an aim, the external factors affecting dispersal are rarely explicitly clear, making it difficult to erect prior hypotheses of expected patterns.…”
Section: Introductionmentioning
confidence: 99%